Chloride ion transport and fate in oilfield wastewater reuse by interval dynamic multimedia aquivalence model. - Hu, Y. (Water Science and Technology)
A surface flow constructed wetland was built up to dispose of oilfield wastewater with a high level of inorganic salt ions. Chlorine ion (Cl−) was selected as an indicator of soil secondary salinization, and an interval dynamic multimedia aquivalence (IDMA) model was developed to investigate the dynamic multimedia environmental (air, water, soil, flora, and groundwater) effects of Cl− in the wastewater irrigation process between 2002 and 2020. The modeled Cl− concentrations were in good agreement with the measured ones, as indicated by the interval average logarithmic residual errors (IALREs) being generally lower than 0.5 logarithmic units. The model results showed that the temporal trends of Cl− concentrations in the multimedia environments represented a relatively steady state. More than 97.00% of the mass exchange was finished between soil and groundwater compartments, and Cl− finally outputted the environmental system by the pathways of advection outflows in the water (71.03%) and groundwater (24.02%). Soil (59.17%) was the dominant sink of Cl−. It was revealed that the high level of Cl− in oilfield wastewater was well treated by the constructed wetland, and there was not a significant environmental effect of soil secondary salinization in the oilfield wastewater reused for the constructed wetland irrigation.